CagA seropositivity associated with development of gastric cancer in a Japanese population. Issue 3 (March 1998) - Shimoyama, T; Fukuda, S; Tanaka, M; Mikami, T; Munakata, A; Crabtree, J E
Abstract : BACKGROUND/AIMS: Infection with Helicobacter pylori strains possessing the cagA gene is associated with increased risk of gastric cancer of the intestinal type. The aims of this study were to investigate whether CagA seropositivity is associated with increasing risk of gastric cancer in a Japanese population that has a much higher incidence of gastric cancer than western populations. METHODS: Eighty one gastric cancer patients and 81 sex and age matched endoscopically evaluated controls were studied. Histologically, 62 cancers were of the intestinal type and 76 were early gastric cancer. Serum CagA IgG antibodies were assayed by enzyme linked immunosorbent assay (ELISA) using purified recombinant CagA protein as antigen. Polymerase chain reaction (PCR) analysis for cagA in H pylori isolates (n = 80) showed that the CagA ELISA had a sensitivity of 83.3% (controls) and 72.5% (cancers). RESULTS: CagA seropositivity was 60% (49 of 81) in cancer patients and 44% (36 of 81) in controls. The odds ratio for the risk of cancer if CagA seropositive was 1.93 (95% confidence interval (CI) 1.01 to 3.68; p < 0.05). In the 57 H pylori positive cancer patients and their matched H pylori positive controls, the odds ratio for the risk of cancer if CagA seropositive was 2.2 (95% CI 1.04 to 4.65; p < 0.05). CONCLUSIONS: These results suggest that CagA seropositivity is associated with increased risk of gastric cancer in Japanese populations.